Comparative study of cast immobilization of wrist in functional position versus conventional palmar flexion in Colles’ fracture - Shrestha, Shriraj; Bhandari, Parash; Dahal, Saurav; Maharjan, Basanta; Bajracharya, Suraj (Journal of Chitwan Medical College, 2020)
Background: Colles’ fracture is a common injury in the elderly population. Although it can be easily reduced, it is difficult to maintain the reduction in the conventional position of the wrist in palmar flexion with a poor functional outcome. Thus our study aimed to compare the radiological and functional outcome of such fractures with the wrist in two different positions of dorsiflexion and palmar flexion. Methods: A prospective, observational study was conducted from April 2019 to March 2020 in the Orthopedics and Emergency department of KIST Medical College Teaching Hospital, Lalitpur, Nepal. Sixty-two patients, 31 in each group, all above 45 years with Colles’ fracture underwent close reduction and below elbow cast immobilization under hematoma block. Maintaining palmar flexion and ulnar deviation at the fracture site, the wrist was immobilized in dorsiflexion and palmar flexion attitude alternatively. During the respective follow-ups, the Demerit Scoring System of Saito was evaluated. Data collection and entry was done using the statistical package for social science version 16 and analyzed by using descriptive and inferential statistics. Results: All fractures were united. At the end of twelve weeks, Saito Scoring System of good to excellent was markedly better in dorsiflexed group 29(93.5%) patients as compared to palmar flexed group 22(71.0%) patients, similarly grip power was also superior in dorsiflexed group 19(61.3%) patients than in palmar flexed group 11(35.5%) patients. Conclusions: Cast immobilization of Colles’ fracture with the wrist in dorsiflexion prevents re-displacement of the fragments resulting in significantly better radiological and functional outcomes.